Sistem Informasi E-commerce Berbasis Web di Toko “Bisacomp” - Fiyan Niizaela Falahie, Al; Irawati, Tri (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2024)
Bisa Comp is a computer store engaged in the trade sector that sells various kinds of laptop products and hardware equipment for computer tools (hardware) and software (software) with official warranties. With the increasing development and increasing needs of the community for services related to the needs of computer products and hardware equipment for computer tools (hardware) and computer software (software), it is necessary to open an up-to-date information system so that all people know. By creating an e-commerce website. Complete profile and product information to make it easier for consumers to find information available at Bisa Comp. The stages carried out are interviews, observations and literature studies. This information system is designed and created with a Content Management System (CMS) and a MySQL database. The e-commerce website that is created can be used as an online marketing network development